Islamic humanism - Goodman, Lenn Evan, 1944- (Oxford University Press, 2003)
Publisher's description: This book is an attempt to explain how, in the face of increasing religious authoritarianism in medieval Islamic civilization, some Muslim thinkers continued to pursue essentially humanistic, rational, and scientific discourses in the quest for knowledge, meaning, and values. Drawing on a wide range of Islamic writings, from love poetry to history to philosophical theology, Goodman shows that medieval Islam was open to individualism, occasional secularism, skepticism, even liberalism.